2018
DOI: 10.1007/s12291-018-0754-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Modulatory Effects of Berberine Chloride on Lipid Profile, Oxidant Status and Insulin Signaling Molecules in Streptozotocin Induced Diabetic Rats

Abstract: The goal of the present study was to evaluate the effect of Berberine chloride (BC) on lipid profile, oxidant status and insulin signaling molecules in Streptozotocin (STZ) induced diabetic rat model. Diabetes was induced in rats by a single dose of intraperitoneal administration of STZ (40 mg/kg b.w). Diabetic rats were treated with BC (50 mg/kg b.w) and glibenclamide (6 mg/kg b.w) for 45 days. BC treated diabetic rats showed significant (p \0.05) decrease in the levels of TC, TG, phospholipids, LDL, VLDL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Simultaneously, as a cause and result of other factors, hyperglycemia is a key mediating factor in the complex etiologic network of DM‐OS 11 . Extensive evidence 26–31 has suggested that BBR regulates glucose metabolism via various mechanisms, such as, stimulating glucagon‐like protein‐1‐dependent insulin secretion, improving insulin resistance by protein kinase C‐mediated upregulation of insulin receptor expression and activation of the IRS‐1 signaling cascade, promoting adenosine monophosphate‐activated protein kinase (AMPK)‐initiated glycolysis, facilitating glucose uptake in adipose tissue by stimulating glucose transporter 1 expression, and inhibiting gluconeogenesis in the liver. In this study, the improved glucose metabolism by BBR treatment hinted that BBR is a potential agent for addressing the adverse effect of hyperglycemia on bone.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, as a cause and result of other factors, hyperglycemia is a key mediating factor in the complex etiologic network of DM‐OS 11 . Extensive evidence 26–31 has suggested that BBR regulates glucose metabolism via various mechanisms, such as, stimulating glucagon‐like protein‐1‐dependent insulin secretion, improving insulin resistance by protein kinase C‐mediated upregulation of insulin receptor expression and activation of the IRS‐1 signaling cascade, promoting adenosine monophosphate‐activated protein kinase (AMPK)‐initiated glycolysis, facilitating glucose uptake in adipose tissue by stimulating glucose transporter 1 expression, and inhibiting gluconeogenesis in the liver. In this study, the improved glucose metabolism by BBR treatment hinted that BBR is a potential agent for addressing the adverse effect of hyperglycemia on bone.…”
Section: Discussionmentioning
confidence: 99%
“…BBR caused the glucose metabolism modulation by the GnRH-GLP-1 and MAPK pathway in the gut (Zhang et al, 2014). The treatment of BBR chloride notably protected the blood components (Chandirasegaran et al, 2017) and significantly reversed the abnormal levels of lipids, oxidant status, and insulin signaling molecules in the diabetic rat model (Chandirasegaran et al, 2019). BBR also reduced the release of lipopolysaccharides and ameliorated inflammation by reducing the level of lipolysaccharide binding protein (LBP), thus alleviating intestinal injury and improving InsR (Cui et al, 2018).…”
Section: In Vivo Activities Against Diabetes and Metabolic Diseasesmentioning
confidence: 99%
“…Berberine is a hydroxyl radical scavenger, and its main metabolite—berberrubine—reveals even greater antioxidative activity than berberine [ 28 ]. It has been reported that after treatment with berberine, the levels of the oxidative stress-related markers decreased while the levels of endogenous antioxidants increased in the tissues of laboratory animals [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%